FAKTOR-FAKTOR YANG DIPERTIMBANGKAN KONSUMEN MENGGUNAKAN JASA MAKE-UP DI KHA BALI WEDDING DALUNG: Studi Pada Konsumen Jasa Make-up di Kabupaten Badung-Bali - I Nyoman Henry Arie Suarthana; Ida Ketut Kusumawijaya; Fitri Marlina Astuti (Journal Research of Management, 2020)
This study studies the factors that influence consumers in using make-up services at Dalung Badung's Kha Bali Wedding and to find out the dominant factors in choosing make-up services at Kala Bali Wedding Dalung Badung. The method used in this analysis is the purposive sampling method. The researcher took a total sample of 84 respondents which were the results of 7 x 12 items representing. The results of this study prove the fact that the factors that influence consumer purchasing decisions using make-up at Dalha Badung's Kha Bali Wedding are the hallmarks of Dalung Badung's Kha Bali Wedding, the strategic location of the company, the payment system, the price according to quality, the choice of location, reference from relatives / family, have used make-up at the company, choose the product that you want. The next factor is the package diversity factor and ease of information.Keywords: factors considered by consumers.